y(y + 4) - y = 6 is a quadratic equation.
TrueFalse

y(y + 4) - y = 6 is a quadratic equation. This is TRUE.

Question

Asked 2/25/2014 9:30:52 AM

Updated 2/26/2014 8:58:53 PM

1 Answer/Comment

Rating

3

y(y + 4) - y = 6 is a quadratic equation.

This is TRUE.

This is TRUE.

Added 2/26/2014 8:58:53 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/28/2014 10:18:23 AM]

Find the line of symmetry for the parabola whose equation is y = 2x 2 - 4x + 1.
**Weegy:** x=y+5/2 **User:** What is the vertex of the parabola whose equation is y = (x + 1)2 + 3?
**Weegy:** Hint: Use ^ to indicate exponents in the future if you do not know how to write the exponents. Example: y = x^2 + 4x - 6 You have to complete the [ square to convert it into vertex form. y = x? + 4x - 6 Group. [ y = (x? + 4x) - 6 Factor y = (x? + 4x) - 6 Add placeholders. y = (x? + 4x + ___) - 6 - 1(___) Notice that the second blank is multiplied by -1 to account for what you had to add to complete the square. Take the coefficient of the x term: 4 Divide it by 2: 4 / 2 = 2 Square it: (2)? = 4 Add 4 to both blanks. y = (x? + 4x + 4) - 6 - 1(4) x? + 4x + 4 is the expanded form of a perfect square binomial. Remember that (a + b)? = a? + 2ab + b?. Apply this to what you have. y = (x? + 4x + 4) - 6 - 1(4) y = (x + 2)? - 6 - 1(4) Simplify the rest. y = (x + 2)? - 6 - 4 y = (x + 2)? - 10 Remember that the vertex form is: y = a(x - h)? + k CHECK: y = (x + 2)? - 10 y = [(x)? + 2(x)(2) + (2)?] - 10 y = (x? + 4x + 4) - 10 y = (x?) + 1(4x) + 1(4) - 10 y = x? + 4x + 4 - 10 y = x? + 4x - 6 TRUE ANSWER: y = (x + 2)? - 10 is the vertex form. Given: y = (x + 2)? - 10 Means: h = -2 Means: k = -10 Means: a = 1 ANSWER: The vertex is at (-2, -10). Since the equation is a function of x and a is positive, the parabola opens upwards. Parabolas that open upwards or downwards have an axis of symmetry that is the same as the h coordinate of the vertex. ANSWER: The axis of symmetry is at x = -2. Remember that y-intercepts have x = 0. Find the value of y when x = 0 by substitution x with 0 in the original equation. y = x? + 4x - 6 y = 0? + 4(0) - 6 y = 0 + 0 - 6 y = -6 ANSWER: The y-intercept is at (0, -6). ] (More)

Question

Expert Answered

Updated 3/12/2014 11:34:55 PM

2 Answers/Comments

The vertex of the parabola whose equation is y = (x + 1)^2 + 3 is (-1, 3)

Added 3/12/2014 11:33:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/8/2014 9:19:58 AM]

27,948,081

questions answered

There are no comments.